Penggunaan Tanah Vertisol Sebagai Bahan Baku Pembuatan Silika - Medya Ayunda Fitri; Farikha Alfi Syahriyah; Yulia Tri Rahkadima (Politeknik Negeri Malang, 2021)
Silica is widely used in industry. The aim of this study was to determine the silica content in vertisol soil in Bringinbendo village. This research was started by soaking the soil in aquadest, then washed 3 times and dried it at 110 ° C for 24 hours. Furthermore, smoothed to 250 mesh size. The second stage is the synthesis of silica using the alkaline extraction method and the treatment of acids. 20 grams of soil powder were extracted in 100 ml NaOH (3, 5, dan 7M) while stirring and heated at 80 ° C. Next, 250 ml of aquadest was added and filtered using Whatman paper. The filtrate was titrated with 5M HCl while stirring until the pH reached 7. The suspension was maintained at room temperature for 24 hours, filtered, and 5 times with aquadest then dried. The results of the mass study were that the greatest silica was found in 7M NaOH concentration at 1 hour, namely 2.59 grams and vertisol soil in Bringinbendo Village had silica content in the medium category with a proportion of 77.7%.